Using Monoclonal Antibody Therapies for Multiple Sclerosis: A Review - Elsbernd PM; Carter JL (Biologics: Targets & Therapy, 2021)
Paul M Elsbernd, Jonathan L Carter Department of Neurology, Mayo Clinic, Scottsdale, AZ, USACorrespondence: Jonathan L CarterDepartment of Neurology, Mayo Clinic, 13400 East Shea Boulevard, Scottsdale, AZ, 85259, USATel +1-480-301-8100Fax +1-480-301-8451Email carter.jonathan@mayo.eduAbstract: Monoclonal antibody therapies have secured an important role in the therapeutic landscape for the treatment of both relapsing and progressive forms of multiple sclerosis due to their potent efficacy, convenient dosing schedules, and well-defined side effect profiles. Each therapy has unique risks and benefits associated with its specific mechanism of action which ultimately guides clinical decision-making for individual patients. This review will summarize the mechanisms of action, evidence leading to their approval, and clinically relevant considerations for each of the current monoclonal antibody therapies approved for the treatment of multiple sclerosis.Keywords: monoclonal antibodies, multiple sclerosis, relapsing, progressive, review